2005
DOI: 10.1128/jb.187.10.3352-3358.2005
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of the High-Pathogenicity Island ofYersinia pseudotuberculosis

Abstract: The horizontal transfer of genetic elements plays a major role in bacterial evolution. The high-pathogenicity island (HPI), which codes for an iron uptake system, is present and highly conserved in various Enterobacteriaceae, suggesting its recent acquisition by lateral gene transfer. The aim of this work was to determine whether the HPI has kept its ability to be transmitted horizontally. We demonstrate here that the HPI is indeed transferable from a donor to a recipient Yersinia pseudotuberculosis strain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
4
40
0
1
Order By: Relevance
“…DNA was obtained by thermolysis of bacteria in a solution containing 50 mM NaOH and 0.25% sodium dodecyl sulfate. The primers (obtained from Proligo France) amplified the int gene of the high pathogenicity island (HPI) (24), the yopM (33), and yopK (forward, 5Ј-CTGCTCATTTACTGAGAACG-3Ј; reverse, 5Ј-CTATAAGTAGAGAGTTTTTCGG-3Ј), genes of the pYV virulence plasmid, the pilR and pilN genes of the type IV pilus locus (10), and the ypmAC or ypmB genes coding for YPM superantigens (15). The housekeeping gene ureB encoding an urease subunit was used as an internal positive control for the PCRs.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was obtained by thermolysis of bacteria in a solution containing 50 mM NaOH and 0.25% sodium dodecyl sulfate. The primers (obtained from Proligo France) amplified the int gene of the high pathogenicity island (HPI) (24), the yopM (33), and yopK (forward, 5Ј-CTGCTCATTTACTGAGAACG-3Ј; reverse, 5Ј-CTATAAGTAGAGAGTTTTTCGG-3Ј), genes of the pYV virulence plasmid, the pilR and pilN genes of the type IV pilus locus (10), and the ypmAC or ypmB genes coding for YPM superantigens (15). The housekeeping gene ureB encoding an urease subunit was used as an internal positive control for the PCRs.…”
Section: Methodsmentioning
confidence: 99%
“…The complex process of horizontal transfer may offer an explanation for this process, which can abolish the expression of HPI genes. Lesic and Carniel (2005) also found that the growth of the HPI recipient strain was inhibited under normal conditions, and virulence was also significantly reduced. Probably due to the process of HPI transfer, homologous recombination in recipient strains leads to the deletion and destruction of growth and virulence genes.…”
Section: Discussionmentioning
confidence: 86%
“…The results of Asn-tRNA loci PCR amplification showed that restructuring also occurred outside the HPI. Lesic and Carniel (2005) also found that HPI had high transfer frequencies at low temperatures and in conditions of low iron abundance, which showed that bacteria were under selective pressure to acquire the complete HPI. After the HPI is obtained by host bacteria, survival in different environments may require adaptive change, in which the function of the HPI is deactivated.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations